Non-invasive techniques to access in vivo the skin microcirculation in patients - Bottino, Daniel Alexandre; Bouskela, Eliete (Frontiers in Medicine, 2023)
The microcirculation is composed of blood vessels with mean internal diameter smaller than 100 µm. This structure is responsible for survival of cells and in the last 50 years its study has become increasingly interesting because it often participates in the pathophysiology of several diseases or can determine better or worse prognosis for them. Due to the growing importance of knowing more about the microcirculation, several techniques have been developed and now it is possible to study its structure or function. In the last 25 years, the cutaneous microcirculation has emerged as an accessible and representative portion of generalized vascular bed allowing the examination of mechanisms of microcirculatory function and dysfunction. This mini review presents several techniques used for non-invasive access to skin microcirculation, such as Nailfold Videocapillaroscopy, Orthogonal Polarization Spectral Imaging, Sidestream Dark Field Imaging, Incident Dark field Illumination, Laser Doppler Flowmetry and Laser Speckle Contrast Imaging applied. The techniques presented will describe which types of variables (structural or functional) can be evaluated, their limitations and potential uses.